Pengaruh Green Marketing terhadap Green Buying Behavior Melalui Environmental Knowledge: Studi pada Unilever Indonesia - Alrizki, Gilang; Kusuma Dewi, Citra (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In resolving the issues looked by the world and the sustainability of life, including climate change, a shared commitment has been formulated in the form of the Sustainable Development Goals (SDGs). One of the companies in Indonesia contributing to the SDGs is Unilever. Unilever has been focused on launching the Unilever Sustainable Living Plan (USLP) since 2010. The reason for this study is to decide the impact of Green Promotion on Green Purchasing Behavior through Ecological Information on Unilever products in Indonesia. Eco-Labeling, Green Advertising, and Green Branding are the three dimensions used in Ali's previous research (2021) to describe environmentally friendly marketing strategies. Eco-Marking is an external confirmation carried out by an organization, taking actions to preserve the climate, and is also included in the eco-label category. Environmental-friendly promotion intends to urge shoppers to utilize harmless to the ecosystem items fully intent on working on ecological security. In the concept of the green marketing, labeling becomes the core of the advertising system in the contemporary business world. This exploration employs a quantitative strategy through various tests, such as legitimacy tests, dependency tests, model fairness tests, speculation tests with intervention factors, and descriptive tests. Based on the results of the mediation analysis, the environmental knowledge variable doesn't intercede the connection between the eco-labeling variable and green buying behavior. The environmental knowledge variable completely intercede the connection between the green advertising variable and green buying behavior. The environmental knowledge variable completely intercede the connection between the green branding variable and green buying behavior.